Inovasi Perancangan OpenChart untuk Memajukan UMKM Kriya di Sumatra Utara - Nurhaliza Mtd, Siti; Annas, Firdaus (Yayasan Lembaga Studi Makwa, 2023)
This study aims to assist craft SMEs (UMKM kriya) in Tambangan, North Sumatra, in maximizing their marketing potential by utilizing Open Chart technology. Currently, the promotion of craft products is still carried out manually and traditionally, making it difficult for these products to gain recognition in wider markets. With the rapid advancement of technology, the adoption of digital tools like Open Chart is expected to help SME actors better understand their business data in a simple and effective way.The research method used is Research and Development (R&D) with stages including Define, Design, Develop, and Decimation. Data was collected through direct interviews with SME actors and observations of their operational activities. The analysis results were then used to design an Open Chart prototype tailored to the needs and usability of SME actors.The results of this study show that Open Chart can assist SME actors in monitoring sales, understanding market trends, and developing more effective marketing strategies. This tool also enables them to expand their market reach and enhance the competitiveness of their products at both local and global levels. This solution is expected to help craft SMEs in Tambangan grow and contribute to the regional economy in a more modern and strategic manner.